Social engineering in the concept of rational and irrational consumer behavior - Krestyanpol, Lyubov (Frontiers in Nutrition, 2022)
In this work, the author researching the process of consumer behavior formation, and considers the possibility of its correction using social engineering methods. The author considers consumer behavior as a separate mandatory element of the product quality monitoring system in the concept of smart consumption. Consumer behavior as a complex of actions and reactions of a public entity in the field of consumption has been considered, assumptions of the economic component of consumer behavior have been formulated, and recommendations for consideration of consumer behavior in the context of social relations have been given. The formation of consumer behavior from the point of view of psychology has been described and considered certain factors that influence the formation of a certain type of consumer behavior. The author has developed strategies for influencing consumer behavior based on social engineering methods. Two approaches to applying strategies to rational and irrational behavior are proposed. The developed strategies will encourage the consumer to participate in the information system of data collection to monitor product quality. The author conducted research, the purpose of which is to determine the target audience that will participate in the process of informing about the product quality monitoring system. As a result of the research, a focus group was formed, which took part in an experiment with the use of strategies to influence consumer behavior.